2021
DOI: 10.3389/fmolb.2020.593040
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, Antimitotic, DNA Binding, Photocatalytic, H2O2 Sensing, and Antioxidant Properties of Biofabricated Silver Nanoparticles Using Leaf Extract of Bryophyllum pinnatum (Lam.) Oken

Abstract: Bryophyllum pinnatum is a perennial herb traditionally used in ethnomedicine. In the present report, silver nanoparticles (AgNPs) were synthesized using B. pinnatum leaf extract. BP-AgNPs were confirmed following UV-Vis spectroscopy with SPR peak at 412 nm and further characterized by FTIR, XRD, SEM-EDX, and TEM. Microscopic images confirmed the spherical shape and ~15 nm average size of nanostructures. BP-AgNPs were evaluated for photocatalytic degradation of hazardous dyes (methylene blue and Rhodamine-B) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…The EDX spectra of both A. alba and P. sylvestris bark extract-derived AgNPs ( Figure 4 A,B, respectively) revealed a pronounced signal for metallic Ag at 3 keV which confirmed the formation of AgNPs. Several other signals were registered for C, N, O, P, and Cl belonging to the compounds in bark extracts acting as capping agents [ 33 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EDX spectra of both A. alba and P. sylvestris bark extract-derived AgNPs ( Figure 4 A,B, respectively) revealed a pronounced signal for metallic Ag at 3 keV which confirmed the formation of AgNPs. Several other signals were registered for C, N, O, P, and Cl belonging to the compounds in bark extracts acting as capping agents [ 33 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of AgNPs was monitored and optimized by recording the UV-Vis spectra of the reaction mixtures in the wavelength range of 350–800 nm [ 29 , 33 , 34 , 35 , 36 ] on a Specord 210 Plus spectrophotometer (Analytik Jena, Jena, Thuringia, Germany). In order to obtain the maximum yield of AgNPs, the synthesis was conducted at various parameters such as pH value of the reaction mixture (2, 4, 6, 8, and 10), AgNO 3 concentration (0.5, 1, 2, and 3 mM), ratio of aqueous bark extract and AgNO 3 (1:9, 2:8, 5:5, 7:3, and 9:1, v / v ), temperature (30, 40, 50, 60, 70, and 80 °C), and reaction time (10, 20, 30, 60, and 120 min).…”
Section: Methodsmentioning
confidence: 99%
“…Mainly, the activity is attributed to the oxidative stress induced by AgNPs and induction of apoptosis via caspase-dependent pathway 20 . In a previous investigation, Bryophyllum pinnatum mediated BP-AgNPs also displayed cytotoxicity against the same cell lines 49 . However, after an incubation period of 24 h, the respective IC 50 values of BP-AgNPs against A431 and B16F10 were 59.5 and 96.6 µg/ml, almost double the IC 50 values of RC@AgNPs.…”
Section: Applications Of Rc@agnpsmentioning
confidence: 73%
“…Another study with onion peel as a reducing agent synthesized AgNPs at 90°C which were spherical in shape with 12.5 nm particle size ( Abdullah et al, 2021 ). Earlier studies on phytofabrication of AgNPs using Bryophyllum pinnatum leaf extract also showed predominance of similar spherical shaped particles with an average size of ∼15 nm ( Chandraker et al, 2021a ). However, anisotropic polydispersed AuNPs were synthesized by LFLE which is in close agreement with triangular, pentagonal, and hexagonal shaped AuNPs synthesized using extracts from various plants such as blackberry, blueberry, pomegranate, and turmeric ( Nadagouda et al, 2014 ; Castillo-Henríquez et al, 2020 ).…”
Section: Resultsmentioning
confidence: 90%